63.2k views
1 vote
PLEASE HELP PRONTO IVE BEEN TRYING FOR AN HOUR

So I have this problem: -2(+3 + -4 + -8 + +7) and when I added all the integers together and multiplied by -2 I get +4 right? Well, when I use distribution I get 6!

WHAT AM I DOING WRONG IVE BEEN TRYING TO FIGURE THIS OUT FOR AN HOUR HELP IM FRUSTRATED SKSKSKSKSK Here's what I did:

-2 x +3, + -2 x +7, + -2 x -4, + -2 x -8
---------------------------------------------------
-6 + -14 + 8 + 18
___________________________
-20 + 26 = 6

heeelp

User Kyle H
by
5.3k points

2 Answers

3 votes
The answer to your question is 4
User Reedcourty
by
4.5k points
6 votes

Answer:

4

Explanation:

-2(+3 + -4 + -8 + +7)

= (-2)(3) + (-2)(-4) + (-2)(-8) + (-2)(7) . . . . . . note that 2ยท8 = 16, not 18

= -6 +8 +16 -14

= 2 +16 -14

= 18 -14

= 4

User Dinesh Singh
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.